Machine Maintenance in the Sabroe Line Using Reliability Centered Maintenance (RCM) and Maintenance Value Stream Mapping (MVSM) Methods - Isna Nugraha; Joumil Aidil Saifuddin; Yekti Condro Winursito (Future Science, 2023)
XYZ is a company that operates in the frozen food industry in particular. The company is a producer of high-quality frozen food products for export, so, naturally, other stakeholders in each division of the company need to work together well. Machine maintenance is a key aspect in maintaining the performance and reliability of industrial equipment. To increase machine maintenance efficiency in this factory, a comprehensive and structured approach is needed. Therefore, this research will discuss the machine maintenance strategy implemented in the Sabroe production line. The two methods that will be the main focus of this research are Reliability Centered Maintenance (RCM) and Maintenance Value Stream Mapping (MVSM). The conclusion obtained by examining the highest Risk Priority Number (RPN) for each component in the blanching machine, it can be concluded that the gearbox component has the highest RPN, namely 216, which is the result of multiplying the Severity, Occurrence, and Detection values. During the period of breakdowns and repairs of the blanching machine, the Mean Time to Failure (MTTF) is found to be 242.2538 hours. Meanwhile, the Mean Time to Repair (MTTR) reaches 172.6 minutes or equivalent to 2.8 hours. The gearbox component requires a repair time of 2.8 hours. The inspection interval for the gearbox component is calculated for 302.01 hours, or every 12 days in a month. Efficiency analysis of maintenance using the Maintenance Value Stream Mapping approach indicates that the percentage of maintenance efficiency reaches 73.2%. Activities that add value require a longer time, around 172.6 minutes, while activities that do not add value require about 63.2 minutes.